PAI–PAK Elementary School Textbooks as an Ideological State Apparatus (ISA): A van Leeuwen Critical Discourse Analysis Framed by Ecofeminism on the Construction of Gender–Ecology in the Independent Curriculum (Merdeka Curriculum) - Setiyawan, Radius; Wijayadi, Wijayadi; Roisiah, Riska Rahayu (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2025)
Purpose – To assess the ideological construction of gender–ecology in Islamic Religious Education (PAI) and Christian Religious Education (PAK) elementary-level textbooks under the Independent Curriculum (Merdeka Curriculum) used in Sekolah Penggerak (2021–2023), addressing the research gap that has not regarded textbooks as a state ideological product Design/methods/approach – A descriptive qualitative study using van Leeuwen’s Critical Discourse Analysis (CDA) combined with ecofeminism. Data: eight books (grades 1–4) published by the Ministry of Education, Culture, Research, and Technology and the Ministry of Religious Affairs; a text–visual documentation study; online interviews with five informants (two teachers, one editor, two authors); purposive sampling; categories of inclusion/exclusion, activation/passivation, role allocation, genericisation/specification; source triangulation and research ethics were applied. The scope is limited to eight books and two subjects. Findings – Identifies patterns of domestication of women; marking of femininity (e.g., the color pink); involvement of women in ecological activities that are subordinate and anonymous, whereas men are named/activated as protectors or givers; women are passivated as recipients of assistance. The integration of gender equality values and ecological awareness is not systematic. The state, through the Ideological State Apparatus (ISA), reproduces patriarchal–anthropocentric discourse. Research implications – Proposes a CDA–ecofeminism rubric–based audit–revision across the entire publishing cycle; editorial–design guidelines (balance of roles, equal naming, avoidance of essentialist visual codes); discourse literacy training for teachers; as well as periodic, transparent evaluations with feedback channels from schools and religious communities.